The influence of parental parenting patterns on achievement motivation and learning motivation of student athletes through social support - Whasilah, Vina; Prasetiyo, Rahayu; Basuki (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
This study aims to analyze the influence of parenting style on achievement motivation and learning motivation among student-athletes, with social support as a mediating variable. The background of this research lies in the importance of parenting in shaping character, achievement drive, and learning motivation, especially for students who are also athletes and face dual challenges in academics and sports. This research employed a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The sample consisted of 81 student-athletes selected through purposive sampling. The research instrument was a Likert-scale questionnaire that had been tested for validity and reliability. The results revealed that parenting style had a significant effect on achievement motivation but not on learning motivation. Social support was found to partially mediate the relationship between parenting style and achievement motivation but did not mediate the relationship with learning motivation. These findings emphasize the importance of social support in strengthening achievement motivation among student-athletes, although improving learning motivation requires additional factors beyond parenting style and social support. This study contributes to the development of more comprehensive coaching strategies for student-athletes by optimizing social support. Future research is recommended to explore other psychological and environmental variables that may influence learning motivation.